PENGEMBANGAN MODUL EDUKASI UNTUK SISWA YANG MEMILIKI KEPERCAYAAN DIRI RENDAH DI SMAN 2 BENGKALIS - Azka Safira; Elni Yakub; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this research to develop education module for student whohave low self confidence. This type of research used is research and development Researchand Development (R&D). for this validator are 2 lecturer of guidance and counseling and2 Counseling Guidance Teachers. Data collection techniques in this study used interviewsand validation questionnaires. The results of this study have compiled a learning modulewith educational material for students who have low self confidence. The results of theoverall module validation test are based assessment showed that average of 3.6 with “verygood” quality. It can be used for lerning guidance and counseling for student.Keywords: Module. Education, Low Self Confidence